Metallic ion release from biocompatible cobalt-based alloy - Dimić Ivana D.; Cvijović-Alagić Ivana Lj.; Kostić Ivana T.; Perić-Grujić Aleksandra A.; Rakin Marko P.; Putić Slaviša S.; Bugarski Branko M. (Chemical Industry and Chemical Engineering Quarterly, 2014)
Metallic biomaterials, which are mainly used for the damaged hard tissue replacements, are materials with high strength, excellent toughness and good wear resistance. The disadvantages of metals as implant materials are their susceptibility to corrosion, the elastic modulus mismatch between metals and human hard tissues, relatively high density and metallic ion release which can cause serious health problems. The aim of this study was to examine metallic ion release from Co-Cr-Mo alloy in artificial saliva. In that purpose, alloy samples were immersed into artificial saliva with different pH values (4.0, 5.5 and 7.5). After a certain immersion period (1, 3 and 6 weeks) the concentrations of released ions were determined using Inductively Coupled Plasma - Mass Spectrophotometer (ICP-MS). The research findings were used in order to define the dependence between the concentration of released metallic ions, artificial saliva pH values and immersion time. The determined released metallic ions concentrations were compared with literature data in order to describe and better understand the phenomenon of metallic ion release from the biocompatible cobalt-based alloy. [Projekat Ministarstva nauke Republike Srbije, br. III 46010 i br. ON 174004]